The Mechanism of Alkene Elimination from Protonated Toluenesulphonamides Generated by Electrospray Ionisation. Issue 4 (August 2016) - Saidykhan, Amie; Ebert, Jenessa; Martin, William H.C.; Gallagher, Richard T.; Bowen, Richard D.
The positive ion electrospray mass spectra of a range of sulphonamides of general structure CH3 C6 H4 SO2 NHR 1 [R 1 = C n H2 n +1 ( n = 1–7), C n H2 n -1 ( n = 3, 4), C6 H5, C6 H5 CH2 and C6 H5 CH(CH3 )] and CH3 C6 H4 SO2 NR 1 R 2 [R 1, R 2 = C n H2 n +1 ( n = 1–8)] are reported and discussed. The protonated sulphonamides derived from saturated primary and secondary aliphatic amines generally fragment to only a limited extent unless energised by collision. Two general fragmentations are observed: firstly, elimination of an alkene, C n H2 n, obtained by hydrogen abstraction from one of the C n H2 n +1 alkyl groups on nitrogen; secondly, cleavage to form CH3 C6 H4 SO2 + . The mechanism by which an alkene is lost has been probed by studying the variation of the intensity of the [M + H – C n H2 n ] + signal with the structure of the alkyl substituent(s) on nitrogen and by monitoring the competition between the loss of different alkenes from protonated unsymmetrical sulphonamides in which two different alkyl groups are attached to nitrogen. This fragmentation is favoured by branching of the alkyl group at the carbon atom directly attached to nitrogen, thus suggesting that it involves a mechanism in which the stability of the cation obtained by stretching the bond connecting the nitrogen atom to the alkyl group is critical. This interpretation also explains the competition between alkene elimination and cleavage to form CH3 C6 H4 SO2 + (and, in some cases, cleavage to form C6 H5 CH2 + or [C6 H5 CHCH3 ] + ).